2008
DOI: 10.1128/iai.01176-08
|View full text |Cite
|
Sign up to set email alerts
|

Infected-Host-Cell Repertoire and Cellular Response in the Lung following Inhalation ofFrancisella tularensisSchu S4, LVS, or U112

Abstract: Francisella tularensis causes systemic disease in humans and other mammals, with high morbidity and mortality associated with inhalation-acquired infection. F. tularensis is a facultative intracellular pathogen, but the scope and significance of cell types infected during disease is unknown. Using flow cytometry, we identified and quantified infected-cell types and assessed the impact of infection on cell populations following inhalation of F. tularensis strains U112, LVS, and Schu S4. Initially, alveolar macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
212
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(233 citation statements)
references
References 34 publications
18
212
1
Order By: Relevance
“…1G). Several recent studies have highlighted the differences between the pathogenesis of F. novicida, LVS, and SchuS4 strain (63)(64)(65) and have shown that infection of mice or macrophages with the former strain results in rapid induction of proinflammatory cytokines, whereas these responses are extremely muted after infection with the latter two strains. F. novicida, which was used as a positive control in intramacrophage lysis studies, underwent significantly higher lysis as compared with F. tularensis LVS or FTL_0325 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…1G). Several recent studies have highlighted the differences between the pathogenesis of F. novicida, LVS, and SchuS4 strain (63)(64)(65) and have shown that infection of mice or macrophages with the former strain results in rapid induction of proinflammatory cytokines, whereas these responses are extremely muted after infection with the latter two strains. F. novicida, which was used as a positive control in intramacrophage lysis studies, underwent significantly higher lysis as compared with F. tularensis LVS or FTL_0325 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Because IL-17Rs are expressed on a wide variety of cell types, including leukocytes and epithelial cells, and many of these cell types can support the growth of Francisella species (13,32,33), we investigated the direct impact of IL-17A on control of LVS growth in host cells. Interestingly, we found that IL-17A can cooperate with IFN-g to inhibit growth of LVS in alveolar epithelial cells and macrophages.…”
Section: Cd8mentioning
confidence: 99%
“…Cells were then washed and immediately stained for surface marker expression using the following fluorescent mAbs: anti-F4/80, anti-CD11b, and anti-CD11c (BD Pharmingen, San Diego, CA). Subpopulations of pulmonary macrophages were categorized as previously described (46 …”
Section: Flow Cytometrymentioning
confidence: 99%